Pengaruh Lingkungan Kerja dan Dispilin Kerja terhadap Kinerja Karyawan pada PT. Upods Karya Indonesia Jakarta - Zefanya Dewitha Yunica; Rosento Rosento (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
PT. Upods Karya Indonesia operates as an electronic cigarette manufacturer, focusing on product quality and details, promoting environmentally friendly vaping systems. The aim of the research is to determine the influence of the work environment and work discipline on employee performance at PT. Upods Karya Indonesia. With a research sample of 54 employees and primary data collection techniques, using the SPSS 20 multiple linear regression data analysis method. The results of the partial hypothesis test (T Test) work environment t value > t table 3,800 > 2,008 significance value 0.00 < 0.05 meaning the work environment has an influence and significant impact on employee performance at PT. Upods Karya Indonesia, results of the partial hypothesis test (T Test) of work discipline t value > t table 6,073 > 2,008 significance value 0.00 < 0.05 meaning that work discipline has a significant and influential effect on employee performance at PT. Upods Karya Indonesia, results of simultaneous hypothesis testing (F Test) work environment and work discipline calculated f value > f table 53,270 > 3.18 significance value 0.00 < 0.05. It can be concluded that the work environment and work discipline simultaneously and significantly influence employee performance at PT. Upods Karya Indonesia.